Dampak hospitalisasi terhadap stress pasien gastritis di perawatan interna di RSUD Namlea kabupaten Buru - Rambu, Sitti Herliyanti; Ilyas, Asmiana Saputri (EcoVision: Journal of Environmental Solutions, 2024)
Hospitalization is a crisis that can increase the client's stress problems while being treated in the hospital. This situation causes feelings of discomfort and stress. The effects of stress will cause manifestations in the form of physical disorders, cognitive changes, feelings, and behavior. Aim to determine the extent of the relationship between the impact of hospitalization on the stress of gastritis patients in the Internal Care Room at Namlea Regional Hospital, Buru Regency. This research is observational analytic with a cross-sectional approach and uses observational analytical methods. Sampling was carried out using a purposive sampling technique of 30 respondents. Data collection uses a questionnaire to determine the threat of serious illness, loss of freedom, medical problems, and financial problems. The data processing technique uses the chi-square statistical test. From the results of this study, significance values were obtained respectively for the threat of disease with stress = 0.001, loss of freedom with stress 0.031, and treatment problems with stress 0.000 where the p-value <0.05. So it can be concluded that there is a relationship between the threat of loss of freedom and treatment for stressful events.